A versatile smoothed particle hydrodynamics code for graphic cards - Schaefer, C. M. (2020)
We present the second release of the now open source smoothed particle hydrodynamics code miluphcuda. The code is designed to run on Nvidia CUDA capable devices. It handles one to three dimensional problems and includes modules to solve the equations for viscid and inviscid hydrodynamical flows, the equations of continuum mechanics using SPH, and self-gravity with a Barnes-Hut tree. The covered material models include different porosity and plasticity models. Several equations of states, especially for impact physics, are implemented. The basic ideas of the numerical scheme are presented, the usage of the code is explained and its versatility is shown by means of different applications. The code is hereby publicly available. (C) 2020 Elsevier B.V. All rights reserved.